Roughness effect on the efficiency of dimer antenna based biosensor - D. Barchiesi; S. Kessentini (Advanced Electromagnetics, 2012)
The fabrication process of nanodevices is continually improved. However, most of the nanodevices, such as biosensors present rough surfaces with mean roughness of some nanometers even if the deposition rate of material is more controlled. The effect of roughness on performance of biosensors was fully addressed for plane biosensors and gratings, but rarely addressed for biosensors based on Local Plasmon Resonance. The purpose of this paper is to evaluate numerically the influence of nanometric roughness on the efficiency of a dimer nano-biosensor (two levels of roughness are considered). Therefore, we propose a general numerical method, that can be applied to any other nanometric shape, to take into account the roughness in a three dimensional model. The study focuses on both the far-field, which corresponds to the experimental detected data, and the near-field, responsible for exciting and then detecting biological molecules. The results suggest that the biosensor efficiency is highly sensitive to the surface roughness. The roughness can produce important shifts of the extinction efficiency peak and a decrease of its amplitude resulting from changes in the distribution of near-field and absorbed electric field intensities.